1989
DOI: 10.1002/esp.3290140204
|View full text |Cite
|
Sign up to set email alerts
|

Structure and stability of the former subglacial drainage system of the glacier De Tsanfleuron, Switzerland

Abstract: A well-developed subglacial drainage system consisting of large cavities developed in the lee of bedrock steps connected together by a network of Nye channels is exposed on an area of recently deglaciated limestone bedrock in front of Glacier de Tsanfleuron, Switzerland. This system covers some 51 per cent of the bedrock surface area, and is believed to have transported the bulk of supraglacially-derived meltwaters through the glacier. Using the cavity hydraulics model of Kamb (1987), it is shown that the geom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 19 publications
2
36
0
1
Order By: Relevance
“…Röthlisberger, 1972;Walder and Hallet, 1979;Nienow et al, 1998); (ii) distributed networks of passageways and cavities (e.g. Lliboutry, 1979;Kamb, 1987;Sharp et al, 1989); (iii) thin water films (e.g. Hallet, 1979;Lappegard et al, 2006); and (iv) Darcian flow through sediments (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Röthlisberger, 1972;Walder and Hallet, 1979;Nienow et al, 1998); (ii) distributed networks of passageways and cavities (e.g. Lliboutry, 1979;Kamb, 1987;Sharp et al, 1989); (iii) thin water films (e.g. Hallet, 1979;Lappegard et al, 2006); and (iv) Darcian flow through sediments (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Shreve 1972). Therefore, it is suggested that a linked cavity system (Walder 1986, Sharp et al 1989) and/or subglacial water sheetflow (Weertman 1972, Alley et al 1987, rather than a well-defined major channel, could be responsible for the supply of meltwater and sediment to the ice-grounding line in the present case. Smaller subglacial conduits are more unstable than large ones, and thus might have switched their position several times during the development of the Teikangas fan.…”
Section: Discussionmentioning
confidence: 72%
“…Formerly glaciated limestone bedrock surface at the Glacier de Tsanfleuron, Switzerland, showing dissolution furrowing (1) on the upstream side of a bedrock bump where pressure-induced melting would have occurred, and subglacial calcite precipitation (2) on the downstream side where low pressures, refreezing and solute concentration would have occurred. Glacier flow was from left to right (modified from Sharp et al,1989).…”
Section: The Development Of Theory Relating Glacier Hydrology and Glamentioning
confidence: 99%
“…Detailed geomorphological map of an area of the recently deglaciated bed of Glacier de Tsanfleuron, Switzerland, showing the distribution of formerly water-filled leeside cavities, Nye channels incised into bedrock, and depressions filled with calcite precipitates (from Sharp et al,1989).…”
Section: Hydrologically-based Challenges To the Two Component Conservmentioning
confidence: 99%